The influence of service quality on patient loyalty through satisfaction and trust: Literature review - Zyainal Arifin, Nur; Karyanti, Dewi; Esti Susanti, Christina (Technium Social Sciences Journal, 2025)
This research discusses the influence of service quality on patient loyalty through satisfaction and trust. Service quality, patient satisfaction, patient trust, and loyalty are very important in community health centers because patients will visit for basic care there before being referred to the hospital. So, there is a need for a scientific study about good service quality and can increase patient satisfaction which has an effect on increasing patient loyalty.